Effect of Debt to Equity, Current Ratio, Return on Assets and Stock Price Fluctuations on Financial Distress in Properties and Real Estate Sector Companies Listed on the Indonesia Stock Exchange - Permatasari, Anggi; Suryadi, Edi (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to determine the role of Debt to Equity Ratio (DER), Current Ratio (CR), Return on Assets (ROA) and Stock Price Fluctuations on Financial Distress, with a focus on the Properties & Real Estate sector listed on the Indonesia Stock Exchange for the 2020-2022 period. A sample of 33 companies was used which was taken by purposive sampling technique. The data analysis technique used is quantitative analysis. This analysis results that DER, CR, and ROA have a partial effect on financial distress, while stock price fluctuations have no effect. The data management procedure is carried out with the help of IBM SPSS 26